Managing Urban Commons: A Multidisciplinary Approach: General Introduction - Quarta, Alessandra; Vercellone, Antonio (Sens public)

(untitled) (Département des littératures de langue française, 2024)
As a part of the Horizon 2020 gE.CO Living Lab project, in October 2020, the University of Turin launched a multidisciplinary call for papers on the main aspects and implications of the urban commons phenomenon in Europe. This presentation introduces the special issue, explaining its contents. It also provides the theoretical framework of the issue and describes the workflow that led to its publication.